SYMBOLIC EXECUTION IN AUTOMATICALLY GENERATIONOF DATA OF SOFTWARE TESTING - Tô Hữu Nguyên; Nguyễn Hồng Tân; Hà Thị Thanh; Đỗ Thanh Mai (Tạp chí Khoa học Đại học Đà Lạt)
In software testing area, all test cases are often generated manually. It time-consumming and costly to complete such task. Symbolic execution is a well-known technique for automatically making the test cases that cover almost every testing criteria in order to deeply discover some errors in complex software systems. In this paper, we present some general points and several results in recent researches about symbolic execution technique. This paper also shows different challenges that need setting in this field such as the explosion of execution paths in a program, the ability of constraint solving, memory modelling or concurrent problems etc. The evaluation of published results is given in this paper as well.